Pan-Genomics in Fruit Crops: Current Progress, Challenges and Future Directions - Anupama Roy; Sarika; Mir Asif Iquebal (Journal of the Indian Society of Agricultural Statistics, 2026)
Pan-genomics captures the full spectrum of genetic diversity within plant species and overcomes the limitations of single reference genomes. By integrating core, dispensable, and unique genomic components, pan-genomic approaches enable comprehensive detection of structural variants, presence–absence variations, and lineage-specific genes that underpin phenotypic diversity, domestication, and environmental adaptation. In plant and horticultural crops, particularly tropical and subtropical fruit species characterized by high heterozygosity, polyploidy, and clonal propagation, pangenomics has revealed extensive hidden variation influencing fruit quality, disease resistance, and stress tolerance that was previously inaccessible using traditional genomics.This review synthesizes the concepts, methodological advances, computational tools, and recent progress in plant pan-genomics, with a focused emphasis on tropical and subtropical fruit crops. We discuss pan-genome construction strategies, graph-based representations, and emerging resources, alongside key applications in trait discovery, evolutionary analysis, and molecular breeding. Current challenges, including limited accession diversity, incomplete functional annotation, and computational complexity, are critically examined. Finally, we highlight future directions toward population-scale, graph-based, and multi-omics–integrated pan-genomes, underscoring their potential to accelerate precision breeding and support the development of climate-resilient, high-quality fruit crop varieties.